1986
DOI: 10.1037/0021-843x.95.3.195
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness and phobia: Effects of stimulus content on human visceral conditioning.

Abstract: Seligman's preparedness theory of phobia is tested in human classical conditioning of skin conductance and heart rate responses. Conditioned stimuli (CSs) were photographs of plants, human artifacts, and phobia-relevant animals. Both aversive tactile and auditory unconditioned stimuli (UCSs) were assessed. Consistent with Ohman's results, electrodermal extinction was slower to phobia-relevant stimuli than to other stimuli (and here, was shown to depend on a tactile UCS); however, unlike Ohman's findings, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
98
1
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(111 citation statements)
references
References 34 publications
10
98
1
2
Order By: Relevance
“…Consistent with Olsson et al (2005), we found no evidence that the explicit endorsement or implicit internalization of racial stereotypes is related to male-targeted race bias in fear extinction. Taken together with previous findings demonstrating that such prepared learning does not extend to other culturally defined fear-relevant stimuli, such as visual images of broken electrical outlets and firearms (e.g., Cook, Hodes, & Lang, 1986), this suggests that our results are not likely to be due solely to the salience of socially transmitted, semantic information reinforcing negative associations with the prepared stimuli. However, our replication of the finding that a reduction in the prepared effect is penetrable via close, intimate contact (Olsson et al, 2005) suggests that developmental triggers or dispositional factors that emerge early in life may facilitate the reduction of out-group fear, thereby increasing out-group contact.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with Olsson et al (2005), we found no evidence that the explicit endorsement or implicit internalization of racial stereotypes is related to male-targeted race bias in fear extinction. Taken together with previous findings demonstrating that such prepared learning does not extend to other culturally defined fear-relevant stimuli, such as visual images of broken electrical outlets and firearms (e.g., Cook, Hodes, & Lang, 1986), this suggests that our results are not likely to be due solely to the salience of socially transmitted, semantic information reinforcing negative associations with the prepared stimuli. However, our replication of the finding that a reduction in the prepared effect is penetrable via close, intimate contact (Olsson et al, 2005) suggests that developmental triggers or dispositional factors that emerge early in life may facilitate the reduction of out-group fear, thereby increasing out-group contact.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the choice of the fear-relevant and fear-irrelevant stimuli needs to be investigated more closely. As described, the vast majority of studies exploring vicarious conditioning of fear reactions used similar or identical objects or pictures of these stimuli (Cook et al 1986;Dimberg 1986;Egliston and Rapee 2007;Gerull and Rapee 2002;McNally and Reiss 1982;Thunberg and Dimberg 2000;reviews by Öhman 1979Öhman and Mineka 2001). Nevertheless, it is possible that the stimuli may not have been completely comparable in terms of familiarity, even to the young toddlers in our study.…”
Section: Discussionmentioning
confidence: 90%
“…Two of the objects were fear-relevant stimuli, one was a curled black and red rubber snake (22 cm diameter) with open jaws, and the other was a black, white, and red rubber spider (13 cm diameter). Spiders and snakes are commonly feared animals and are theoretically held to be biologically prepared for fear conditioning (Cook et al 1986;Seligman 1971; reviews by Öhman 1979Öhman and Mineka 2001). The other two objects were fearirrelevant stimuli (Cook et al 1986; reviews by Öhman 1979Öhman and Mineka 2001), a brown and white mushroom (15 cm height) and a white and green flower (20 cm height).…”
Section: Measures and Materialsmentioning
confidence: 99%
See 2 more Smart Citations